Long-noncoding RNAs as epigenetic regulators in neurodegenerative diseases - Paola Ruffo; Francesca De Amicis; Emiliano Giardina; Francesca Luisa Conforti (Neural Regeneration Research, 2023)
The growing and rapid development of high-throughput sequencing technologies have allowed a greater understanding of the mechanisms underlying gene expression regulation. Editing the epigenome and epitranscriptome directs the fate of the transcript influencing the functional outcome of each mRNA. In this context, non-coding RNAs play a decisive role in addressing the expression regulation at the gene and chromosomal levels. Long-noncoding RNAs, consisting of more than 200 nucleotides, have been shown to act as epigenetic regulators in several key molecular processes involving neurodegenerative disorders, such as Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis and Huntington’s disease. Long-noncoding RNAs are abundantly expressed in the central nervous system, suggesting that their deregulation could trigger neuronal degeneration through RNA modifications. The evaluation of their diagnostic significance and therapeutic potential could lead to new treatments for these diseases for which there is no cure.